Hypothermia with Extreme Bradycardia following Spinal Cord Infarction of Septic Origin - Philippe Hantson; Thierry Duprez (Case Reports in Neurological Medicine)
Among other autonomic dysfunctions complicating acute spinal cord injury, deep hypothermia is rare but may induce serious cardiovascular complications. There are few pharmacological options to influence hypothermia. A 66-year-old woman was transferred to the intensive care unit (ICU) for serious cardiac arrhythmias (atrial fibrillation and asystole) in the context of a deep hypothermia (axillary temperature below 32°C). She had been admitted to the hospital two months before for an acute L4-L5 infectious spondylodiscitis without any initial neurological deficit. After surgery for epidural abscess drainage, she became paraplegic due to spinal cord infarction (from C7 to T6 levels) in the upper territory of the anterior spinal artery. In the ICU, the patient experienced several episodes of asystole and hypotension associated with a core body temperature below 35°C. Common causes of hypothermia (drugs, hypothyroidism, etc.) were excluded. A definitive pacemaker had to be inserted, but hypotension persisted. The prescription of oral progesterone (200 mg·d−1) helped to maintain a core temperature higher than 35°C, with a withdrawal of vasopressors. This case report illustrates that patients with incomplete spinal cord injury may present with delayed and deep hypothermia leading to serious cardiovascular complications. Progesterone could be able to influence positively central and peripheral thermal regulation.